SME Credit Access in Nigeria vs. the Czech Republic : A Comparative Analysis. - Dzvikidzo, Mitchel Kudzai; Rajl, Jiří; Málek, Jiří, 1953-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This research compares the credit access of SMEs in the Czech Republic and Nigeria, focusing on the institutional, economic, and regulatory factors influencing loan availability in both countries. Using structured questionnaires and a cross-sectional quantitative approach, the study finds that Nigerian SMEs face significant barriers, such as high interest rates, strict collateral requirements, and institutional inefficiencies like corruption and regulatory challenges. In contrast, Czech SMEs benefit from a more stable financial system, transparent lending processes, and effective government support. The study applies Financial Constraint Theory and Institutional Theory to highlight the impact of institutional and legal frameworks on credit access. It suggests that Nigeria improve government support, develop alternative finance sources, streamline regulations, and reform financial infrastructure to foster inclusive finance systems and long-term economic growth.
Vedoucí práce: Jiří Rajl
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses